Perencanaan Sumber Daya Manusia dan Kompetensi Karyawan terhadap Kinerja Karyawan pada Kedai Kopi Kala Senja Karawang - Gina Fauziah; Anggi Pasca Arnu (Jurnal Mirai Management, 2022)
Its operational activities at coffee shops at dusk karawang, got a little obstacles, especially related to the performance of employees who experienced a slight decrease. The decrease in employees' work is not due to inadequate company facilities but rather because it is caused by the condition of employees who are less eager in carrying out their work. To overcome all these obstacles, it is necessary to plan human resources for recruitment and selection of prospective employees in the future. Coffee shop at dusk Karawang, is one of the coffee industry that is much in demand by young people around the karawang area. Planning human resources in coffee shops at dusk by planning employees in accordance with the needs of employees in coffee shops are also educated differently, the development of the times, the education needed for human resources is also higher. Human resource planning is the basis for the preparation of work programs for work units that handle human resources in the organization. One aspect of the work program is the procurement of manpower that is useful to strengthen the existing workforce in order to improve the organization's ability to achieve its goals and objectives. The recruitment and selection process is expected to gather an adequate number of applicants. Storage of job information for coffee shops at dusk karawang whose workforce is relatively small then internal sources are not an alternative, but a source from outside the company.. Keywords: Human Resource Planing, Recruitmen, Selection